Strategi Pengembangan Pemasaran â€œKamsia Bobaâ€ Sebagai Salah Satu Produk UMKM di Tambun Selatan - Resti Meliana Putri; Tyna Yunita; Alfia Dwi Cahyani; Indra Samuel (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Nowadays, various brands and types of viral drinks continue to emerge in Indonesia. Boba drink is one of those kinds of popular drinks, which originated from Taiwan and has become a popular beverage throughout the world, including in Indonesia, especially among youths and young adults. Boba drink contains high levels of sugar and calorie and is part of the larger group of sugarsweetened beverage (SSB). Boba shops generally offer various beverage flavors, toppings, sizes, choices of sugar and ice level that can be personalized. . The "KAMSIA BOBA" beverage business is a business engaged in the beverage sector which has a different concept from other drinks. The vision of "KAMSIA BOBA" is to provide a different experience to buyers, as well as provide the best and memorable service so that customers always want to come back. The target market for "KAMSIA BOBA" is for the lower middle class but does not rule out also for the upper class who have a lifestyle and a penchant for drinking sweet and cold drinks both to take home. Several marketing strategies implemented by "KAMSIA BOBA" namely social media and direct marketing.